2006
DOI: 10.1086/498528
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Concurrent and TreatedAncylostoma ceylanicumHookworm Infections on the Immunogenicity of a Recombinant Hookworm Vaccine in Hamsters

Abstract: These results suggest that hookworm infections have an immunomodulatory effect by impairing the immune response to an exogenous antigen during infection. The hookworm-associated immunodepression may have important implications for design of clinical trials of human vaccines and vaccination strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…The results presented here confirm previous observations that A. ceylanicum infection is associated with impaired lymphocyte proliferation (23,45), a phenomenon that has also been observed in filarial nematode infections (25,26,54). By day 70 p.i., there were very few adult worms remaining in the intestine (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented here confirm previous observations that A. ceylanicum infection is associated with impaired lymphocyte proliferation (23,45), a phenomenon that has also been observed in filarial nematode infections (25,26,54). By day 70 p.i., there were very few adult worms remaining in the intestine (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have attempted to probe the mechanisms underlying this phenomenon in human and/or laboratory animal hosts (23,45,46). In the present study, we utilized the hamster model of A. ceylanicum to characterize the modulation of host cellular immune responses and potential mechanisms underlying such immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies have shown that elimination of helminth parasites before immunization seems to restore normal vaccine responsiveness. [26][27][28][29] In conclusion, our study adds additional support to earlier observations of an association between the presence of intestinal helminth infection and the development of clinical malaria.…”
Section: Discussionsupporting
confidence: 87%
“…An antibody titer reduction following larval challenge is a common phenomenon for hookworm vaccine trials (43,69), putatively because of antibody absorption by specific antigen produced by the challenged hookworms. No efforts were made to further characterize the cytokine responses, although some hamster reagents are beginning to become available (24,42). Only hamsters vaccinated with rNa-GST-1 achieved protection levels comparable to those reported previously with Ac-GST-1 (65,69).…”
Section: Discussionmentioning
confidence: 83%